A Retrospective Study of Unicompartmental Knee Arthroplasty Functional Outcome and the Incidence of Medial Meniscus Posterior Root Tear in Spontaneous Osteonecrosis of the Knee. (3rd May 2021) - Wu, Po-Ju; Lin, Tsung Yu; Lu, Yung Chang
Abstract : Background . Spontaneous osteonecrosis of the knee (SONK) can lead to severe knee osteoarthritis predominantly localized to the medial compartment. We aimed to determine whether unicompartmental knee arthroplasty was an effective treatment for primary SONK. Methods . We analyzed the functional outcomes in 23 patients with SONK (with a magnetic resonance imaging- (MRI-) confirmed diagnosis) who underwent UKA at a single center. The mean follow-up time was 67 months post-UKA. Results . Significant improvements in function were indicated by reduced Oxford Knee and Visual Analogue Scale scores after UKA, and there were no specific complications after the procedures. The incidence of MRI-identified medial meniscus posterior root tear (MMPRT) was 69.6% (16/23). Conclusion . Unicompartmental arthroplasty for SONK is less destructive to the native knee structure than total knee arthroplasty but can achieve comparable prognosis with strict patient selection. While the precise etiology of SONK is unknown, one theory posits that a MMPRT may change the biomechanical circumstances of the knee joint, leading to osteonecrosis. Although not confirmatory, the high prevalence rate suggests that MMPRT may have a key role in the development of SONK. UKA is an effective treatment option for SONK, resulting in significant functional improvement. Long-term (>10 years) outcomes should be investigated.